Pensando a Diáspora Atlântica - Silva, Lúcia Helena Oliveira; Xavier, Regina Célia Lima (Universidade Estadual Paulista Julio de Mesquita Filho, 2018)
ABSTRACT The text seeks to discuss the different meanings that the term diaspora has assumed since its emergence in the early years of the twentieth century through the debates in the History of Africa, History of the Atlantic Diaspora and the contemporary senses

RESUMO O texto procura discutir os diferentes significados que o termo diáspora tem assumido desde seu o surgimento nos primeiros anos do século XX passando pelos debates na História da África, História da Diáspora Atlântica e os sentidos contemporâneos.
Thinking about the Atlantic Diaspora
Keywords: Diaspora; History of Africa; History of the Diaspora; Pan-Africanism; Diáspora; História da África; História da Diáspora; Pan-Africanismo